Chemoenzymatic synthesis of an α-1, 6-glucan-based conjugate vaccine against Helicobacter pylori. (15th April 2022) - Altman, Eleonora; Chandan, Vandana; Harrison, Blair A; Schur, Melissa; Goneau, Marie-France; Li, Jianjun; Gilbert, Michel
Abstract: In this study, we investigated the utility of glycoconjugates based on a linear α-1, 6-glucan chain synthesized using a recombinant α-1, 6-glucosyltransferase from the 26695 strain of Helicobacter pylori . Capillary electrophoresis–mass spectrometry analysis confirmed the main product to contain 9–10 sequentially added α-1, 6-linked glucose residues. This was consistent with a length of α-1, 6-glucan structure present in the outer core region of H. pylori lipopolysaccharide (LPS) from strains 26695 and 26695 HP0826::Kan. The synthetic α-1, 6-glucan was conjugated to either bovine serum albumin or tetanus toxoid and immunological properties of resultant glycoconjugates investigated. The conjugates were immunogenic in rabbits and mice and induced strong and specific IgG responses against purified LPS from typeable and nontypeable α-1, 6-glucan-positive H. pylori strains. Furthermore, the post-immune sera from rabbits that received the conjugates were bactericidal and cross-reacted with selected clarithromycin-resistant and clarithromycin-susceptible clinical isolates of H. pylori . This technology offers a novel approach to the design of a synthetic carbohydrate-based vaccine against H. pylori .